2008
DOI: 10.1016/j.spmi.2007.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz applications of carbon nanotubes

Abstract: We formulate and justify several proposals utilizing unique electronic properties of carbon nanotubes for a broad range of applications to THz optoelectronics, including THz generation by hot electrons in quasi-metallic nanotubes, frequency multiplication in chiral-nanotube-based superlattices controlled by a transverse electric field, and THz radiation detection and emission by armchair nanotubes in a strong magnetic field. c 2007 Elsevier Ltd. All rights reserved. Keywords: Carbon nanotubes; Terahertz radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 42 publications
1
88
0
1
Order By: Relevance
“…We have shown that manipulating the size of the band gap allows one to exclude from the discrete spectrum certain low-lying quantum states, for example, the ground state, in stark contrast to the nonrelativistic case. The band gap can be controlled, e.g., in the case of carbon nanotubes, by applying an external field [48][49][50][51][52] or via strain [56] or, in graphene nanoribbons, by choosing certain nanoribbons with a desirable geometry [57]. Alternatively, the strength of the interaction potential can be controlled by having multiple charged impurities [58] or changing the dielectric environment.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that manipulating the size of the band gap allows one to exclude from the discrete spectrum certain low-lying quantum states, for example, the ground state, in stark contrast to the nonrelativistic case. The band gap can be controlled, e.g., in the case of carbon nanotubes, by applying an external field [48][49][50][51][52] or via strain [56] or, in graphene nanoribbons, by choosing certain nanoribbons with a desirable geometry [57]. Alternatively, the strength of the interaction potential can be controlled by having multiple charged impurities [58] or changing the dielectric environment.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 SWCNTs with different chiralities exhibit either semiconducting or metallic properties, providing great flexibility for a variety of THz and plasmonic applications, including sources, [5][6][7] detectors, 3,5 antennas, 8,9 and polarizers.…”
Section: Introductionmentioning
confidence: 99%
“…In the above consideration we have only considered the one valley regime, the full treatment of the problem requires that all valley and spin quantum numbers be taken into account, in this instance the number of different types of excitons associated with a given carbon nanotube spectrum branch rises to 16 [54]. In principle this can be accommodated into the above model by modifying the parameters of the potential, consequently all excitons be them dark or bright should have a binding energy within the band gap, ergo for narrow gap tubes, at room temperature, they should be fully ionized and the direct inter-band transitions [42,43,49,45] will govern the emission in the terahertz range.…”
Section: Solution Of the Dirac Equation For The Hyperbolic Tangent Pomentioning
confidence: 99%
“…It has also been demonstrated that the binding energy of certain short range potentials scale with the bandgap and therefore excitonic effects should not dominant optical processes in narrow-gap nanotubes [38,40]. Indeed the typical curvature-induced band gap lies in the desirable terahertz frequency range which has led to a variety of promising proposals of utilizing them in terahertz applications [42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%